Perceived Attitudes of Pet Owners About Their Pets During the COVID-19 Pandemic - Halbreich, Eli D. (Tufts Archival Research Center, 2021)
The global COVID-19 pandemic has impacted the lives of both people and animals worldwide. Research conducted during the early phases of the pandemic indicated mixed but generally positive relationships with pets, which were exacerbated both positively and negatively during the early lockdown phases of the pandemic. This longitudinal study of U.S. residents (n = 63) sought to collect novel data related to the perceived attitudes toward, attachment to, and relationship with pets held by participants at two points during the COVID-19 pandemic. Many participants reported a positive relationship with their pets and appreciated the increased amount of time they could spend with them during the pandemic. Some participants noted an increase in negative behaviors, such as separation anxiety, in their pets. This study contributes to a body of research collected within the context of the COVID-19 pandemic in the U.S.; Thesis (B.S.)--Tufts University, 2021.; Submitted to the Dept. of Psychology.; Committee: Dr. Alexander Queen, Dr. Megan Mueller, Dr. Deborah Linder.; Keywords: pets, COVID-19, human-animal interaction, attitudes, attachment.